Identifying potential hotspots of groundwater-climate interaction in the Kalahari Aquifer System, Upper Zambezi Basin, Southern Africa - Kawawa Banda; Christopher Shilengwe (Journal of Hydrology: Regional Studies, 2025)
Study area: Upper Zambezi Catchment, Southern Africa Study focus: Climate change influence on groundwater is still poorly understood especially in developing countries with a limited monitoring network. In this study, groundwater-climate interactions are investigated for the Kalahari Aquifer, an alluvial aquifer system. Three datasets were used that include Standard Precipitation Evapotranspiration Index (SPEI) data from 1920 to 2022, GRACE groundwater storage anomaly (GWA) data from 2009 to 2022 and climate mode (ENSO, Atlantic Multi-decadal Oscillation (AMO) and Pacific decadal oscillation (PDO) from 1950 to 2022. New hydrological insights for the region: Using SPEI, it was found that severe droughts (SPEI < −2) occurred in 1991/92, 1994/95, 1997/98, 2001/02, 2004/05, 2011/12, 2015/16, 2018/19 likely impacting groundwater storage. SPEI aggregated to 3 months (SPEI-3) correlated with GRACE groundwater storage annomaly (GWA) data with an R2 of ∼0.5. This was indicative of short-term response to effects of droughts. Nino 3.4 (ENSO) and AMO affect groundwater in time scales of inter-annual (4–8 years) and inter-decadal (32–64 years) repeat cycles. Spatially, based on geographysical weighted regression (GWR), SPEI-3 showed strong correlation (R2 = 0.6–0.9) predominately on the western regions of the Kalahari Aquifer, whereas, the southern portions has a low R2 (< 0.4) likely controlled by aquifer structure and water table dynamics hence spatial heterogenity. Adaptation to climate influence on groundwater will require intervention that balance management and technical interventions.